2011
DOI: 10.1016/j.amjcard.2011.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection and Prediction of Cardiotoxicity in Chemotherapy-Treated Patients

Abstract: As breast cancer survival increases, cardiotoxicity associated with chemotherapeutic regimens such as anthracyclines and trastuzumab becomes a more significant issue. Assessment of the left ventricular (LV) ejection fraction fails to detect subtle alterations in LV function. The objective of this study was to evaluate whether more sensitive echocardiographic measurements and biomarkers could predict future cardiac dysfunction in chemotherapy-treated patients. Forty-three patients diagnosed with breast cancer w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
456
2
30

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 619 publications
(532 citation statements)
references
References 13 publications
22
456
2
30
Order By: Relevance
“…5 Although multicenter studies 20,21 and a recent meta-analysis 13 support the use of speckle tracking echocardiography in screening for cardiotoxicity in patients treated with anthracyclines and trastuzumab, it is still not used routinely in clinical practice. The results of our study are in line with those of previous studies, and highlight the value of longitudinal strain for both assessment of subclinical cardiotoxicity and identification of patients at high risk of developing CIC.…”
Section: Discussionmentioning
confidence: 99%
“…5 Although multicenter studies 20,21 and a recent meta-analysis 13 support the use of speckle tracking echocardiography in screening for cardiotoxicity in patients treated with anthracyclines and trastuzumab, it is still not used routinely in clinical practice. The results of our study are in line with those of previous studies, and highlight the value of longitudinal strain for both assessment of subclinical cardiotoxicity and identification of patients at high risk of developing CIC.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter study comparing echocardiographic parameters in patients with HF, global longitudinal strain (GLS) assessment, a parameter evaluating longitudinal aspect of myocardial contraction using deformation imaging, appeared to have a higher and more reliable prognostic value than LVEF for the prediction of cardiac events and cardiac deaths [20]. 2D speckle tracking strain has already been evaluated in studies for a total of more than 700 patients concomitantly to the administration of cardiotoxic anticancer agents, with encouraging results concerning its capability to diagnose subclinical LV dysfunction of subsequent clinical relevance [21][22][23][24][25][26][27]. Based on these data, serial strain measurements are suggested during anticancer treatment [11••].…”
Section: Imaging Techniques Echocardiographymentioning
confidence: 99%
“…High-sensitive troponins assays may have a greater interest for the detection of subclinical myocardial damage. Sawaya et al recently demonstrated that highsensitive Tn-I assays in combination with echocardiography strain imaging increase the accuracy of early detection and prediction of CTRCD in breast cancer patients treated with anthracyclines and trastuzumab [22,24]. The ASE/EACVI consensus document recommends serial Tn-I levels be drawn with a chemotherapy regimen potentially associated with type I or type II toxicities or in case of their sequential administration [11••].…”
Section: Circulating Biomarkersmentioning
confidence: 99%
See 2 more Smart Citations